In armorum artibus spectabiles satis sunt : relações políticomilitares e poder monárquico na trajetória visigoda durante a antiguidade tardia (332-711) - Prata, Rafael Costa (2016)
In our thesis, it's analyzed the cadre of the political and military relations operated by the Visigoths face to the various political centers in which had contact during the Late Antiquity. We emphasized, specially, to the creation of the conflicts that, inevitably, erupted of the complex cadre of tension, conflicts and negotiations that were established between that cores. From a sequence of promulgated precepts by the Roman imperators and Visigoth monarchs, in various legal documents that produced during the Late Antiquity, we analyzed, also, how was conceived its political and military organization. Therefore, our research has an analytics condution marked by a view focused on the foreign policy and also on the constituent elements of the internal policy of the regnum. To effectuate this research, we used the theorical and methodological assumptions provided by the concept of Late Antiquity. This concept being stepped in a long term view, it was an important sinew deeply exact to the purposes of our research, once it was allowed to us to pay attention to a sequence of distinctive aspects of a specific past, but they ended up staying on the late-old picture, that it was constituted as the center of all of our analysis. Proving the perception that the History is composed of both disruptions and by continuities.